KOMPARASI KINERJA BANK PEMERINTAH DAN BANK SWASTA YANG GO PUBLIK DI BURSA EFEK INDONESIA PERIODE TAHUN 2008-2011 (Students' Journal of Accounting and Banking, 2013)
The purpose of this study was to examine and analyze whether there are differences in the performance of government banks and private banks that go public in Indonesia Stock Exchange in the period 2008-2011. Financial performance indicators measured by CAMEL comprising CAR ratios, RORA, NPM, ROA and LDR. The population in this study are government banks and private banks recorded IDX years 2008-2011. Sampling method used was purposive sampling technique. The method of analysis is the different test Anova. The data analysis technique used is the analysis of different test Mann-Whitney test. The results showed that there is no difference between the CAR, NPM and LDR between State Bank and Private Banks. While the Return on Risk Assets and Return on Assets and the State Bank Private Bank there is a differenceKeywords: Capital Adequacy Ratio, Return on Risk Assets, Net Profit Margin, Return on Assets dan Loan to Deposit Ratio